Case Report: Idiopathic intramural hematoma of the jejunum in a French Bulldog - Kim, Yeon-Jin; Choi, Dong-Min; Kang, Jong-Il; Kim, Dong-Yeong; Nam, Chan-Sik; Lee, Kwang-Sup; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
This case report describes clinical and diagnostic features of an idiopathic jejunal intramural hematoma in a dog presenting with non-specific gastrointestinal symptoms. A 2-year-old neutered male French Bulldog was presented with vomiting, abdominal pain, and chronic soft stools persisting for 2 weeks, with no history of trauma or dietary indiscretion. Physical examination revealed abdominal distension and palpable discomfort. The complete blood count (CBC) showed leukocytosis with neutrophilia, accompanied by signs of dehydration. Serum chemistry revealed no significant abnormalities, although mild electrolyte imbalances were observed. The canine pancreatic lipase immunoreactivity (cPLI) test was within the reference range and the C-reactive protein (CRP) level was slightly elevated. Ultrasonography revealed a heterogeneous mass in the jejunal region, which was suspected to be a hematoma. An exploratory laparotomy was performed, and the affected jejunal segment was surgically resected. Histopathological examination confirmed the mass as an intramural hematoma. Additionally, coagulation profiles revealed no remarkable findings. The cause of the hematoma was determined to be idiopathic after excluding other possible causes. This case highlights the importance of considering intramural hematomas in the differential diagnosis for dogs presenting with non-specific gastrointestinal symptoms, even in the absence of trauma and coagulation abnormalities.